Effects of process parameters on the properties of brake pad developed from seashell as reinforcement material using grey relational analysis - Abutu, J.; Lawal, Sunday Albert; Ndaliman, Mohammed Baba; Lafia-Araga, Ruth Anayimi; Adedipe, Oyewole; Choudhury, Imtiaz Ahmed (Elsevier, 2018)
Over the years, asbestos was used as reinforcement material in brake pads production. However, due to its carcinogenic nature, it has lost its favor and there is need to find an alternative material. In this study, brake pads were produced from locally sourced non-hazardous raw materials using grey relational analysis. The materials used for production include seashell, epoxy resin (binder), graphite (friction modifier) and aluminum oxide (abrasive). Twenty- seven different samples were produced using seashell as reinforcement material by varying the process parameters. Rule of mixture was used for formulation and a weight percent of 52% reinforcement, 35% binder, 8% abrasive and 5% friction modifier were used for production. Grey relational analysis was conducted in order to scale the multi-response performance to a single response. The results indicate that optimum performance can be achieved with 14 MPa molding pressure, 160 °C molding temperature, 12 min curing time and 1 h heat treatment time. Analysis of variance shows that curing time has the least significant effect on the mechanical properties, while curing time of 24.26% and 55.23% has the most significant effect on coefficient of friction and wear rate respectively on the brake pad developed.